Customers' perceptions as an antecedent of satisfaction with online retailing services - Peter Mwencha; Stephen Muathe (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2018)
The assessment of antecedents of customer satisfaction has become very important for the success of online retailing services. This paper reports the results of a study that investigated the antecedent role of customers' perceptions vis-a-vis satisfaction with online retailing services. While the study model conceptualizes customers' perceptions as a composite variable made up of three dimensions (perceived attributes, perceived risk and perceived value) prescribed by four established information systems (IS) and consumer behaviour frameworks, namely the Technology Acceptance Model (TAM), Perceived Risk Theory (PRT), Theory of Consumption Values (TCV) and Expectations-Artifact Model of Satisfaction (EAMS), it does not specify how the different perceptual factors influence online satisfaction; instead it aggregates all three dimensions into a higher-order construct called "customers' perceptions" and tries to understand the nature of relationship between the composite independent variable and the dependent variable. It employed a descriptive, correlational survey design whereby the response data collected from 240 registered users of 6 online retailers was analyzed using both descriptive as well as inferential statistics. The linear regression analyses indicate that the model provides a statistically significant explanation of the variation in consumers' online retailing satisfaction. The study also found empirical support for customers' perceptions as an antecedent of satisfaction with online retailing services.
Keywords: M00; M31; 650; online retailing; customer satisfaction; perceptions; e-commerce; online consumer behaviour